Access to parks and recreational facilities, physical activity, and health care costs for older adults: Evidence from U.S. counties. (27th May 2019) - Sato, Mikihiro; Inoue, Yuhei; Du, James; Funk, Daniel C.
Abstract: Although research has documented the health benefits of physical activity and use of park and recreational facilities, the relationships of these factors to healthcare costs remain unexplored at the population level. Building upon a social-ecological model, we analyzed county-level data to examine the extent to which physical activity rate and access to parks and recreational facilities were related to the healthcare costs for older adults (i.e., those 65 years and above) in U.S. counties. The results revealed that older adults' physical activity rate in a county was negatively associated with the county's healthcare costs of these adults. Also, access to parks and recreational facilities was negatively associated with older adults' healthcare costs through the physical activity rate. These findings indicate that access to parks and recreational facilities correlates with increased physical activity levels among older adults, which might reduce their healthcare costs in communities.